Guatemala: ClimBeR Inception Workshop Report - Valencia, Lina; Navarro Racines, Carlos Eduardo; Madurga Lopez, Ignacio M.; Veeger, Marieke; Rose, Sabrina; Loboguerrero Rodriguez, Ana María; Hellin, Jonathan (CGIAR System Organization, 2022)
The CGIAR Initiative on Climate Resilience, ClimBeR, aims to transform the climate adaptation capacity of food, land, and water systems in Guatemala and five other low- and middle-income countries, ultimately increasing the resilience of smallholder production systems to withstand severe climate change effects like drought, flooding, and high temperatures.